Efficient hole extraction with Eu3+-doped CsPbBr3 QD interface modification for HTL-free CH3NH3PbI3:Na perovskite solar cells. (October 2022) - Zhang, Wenhu; Lv, Pin; Li, Yujiao; Wu, Yangqing; Dong, Jia; Wang, Wenzhi; Sun, Hairui; Cao, Bingqiang
Highlights: Eu 3+ -doped CsPbBr3 QD interface modification solves energy level mismatch. Grain boundary defects of MA(Pb0.99 Na0.01 )I3 films passivated by Cs(Pb1-x Eux )Br3 QD. Cs(Pb1-x Eux )Br3 QD interface modification improves device efficiency by 1.5 times. Cs(Pb1-x Eux )Br3 QD makes the surface energy level of perovskite layer bend upward. EBIC demonstrated Cs(Pb1-x Eux )Br3 QD modification improves hole collection ability. Abstract: Hole transport layer free perovskite solar cells (HTL-Free PSCs) have attracted extensive attention due to their advantages of simple structure and low cost. However, due to the serious energy level mismatch caused by the direct contact between the perovskite layer and the opposite electrode, the space for improving the efficiency of HTL-Free PSCs is greatly limited. We use Eu 3+ doped CsPbBr3 quantum dots (QD) to modify the interface between MAPbI3 :Na layer and C electrode, and study its effect on the surface defect passivation, interface energy level arrangement and carrier transport behavior in the device. It was found that compared with the interfacial modification of CsPbBr3 QD alone, the interfacial modification of CsPbBr3 :Eu QD could effectively solve the problem of energy level mismatch in HTL-Free PSCs, resulting in a remarkable improvement of conversion efficiency from 9.01 % to 12.95 %. Furthermore, electron beam induced current (EBIC) was used to prove that CsPbBr3 :Eu QD interface modification significantly improved the hole collection ability. This provides an experimental basis and theoretical guidance for the optimization of the efficiency of other types of transport layer free photovoltaic devices.